The Electronic Conductivity of Single Crystalline Ga‐Stabilized Cubic Li7La3Zr2O12: A Technologically Relevant Parameter for All‐Solid‐State Batteries. Issue 16 (11th June 2020) - Philipp, Martin; Gadermaier, Bernhard; Posch, Patrick; Hanzu, Ilie; Ganschow, Steffen; Meven, Martin; Rettenwander, Daniel; Redhammer, Günther J.; Wilkening, H. Martin R.
Abstract: The next‐generation of all‐solid‐state lithium batteries need ceramic electrolytes with very high ionic conductivities. At the same time a negligible electronic conductivity σeon is required to eliminate self‐discharge in such systems. A non‐negligible electronic conductivity may also promote the unintentional formation of Li dendrites, being currently one of the key issues hindering the development of long‐lasting all‐solid‐state batteries. This interplay is suggested recently for garnet‐type Li7 La3 Zr2 O12 (LLZO). It is, however, well known that the overall macroscopic electronic conductivity may be governed by a range of extrinsic factors such as impurities, chemical inhomogeneities, grain boundaries, morphology, and size effects. Here, advantage of Czochralski‐grown single crystals, which offer the unique opportunity to evaluate intrinsic properties of a chemically homogeneous matrix, is taken to measure the electronic conductivity σeon . Via long‐time, high‐precision potentiostatic polarization experiments an upper limit of σeon in the order of 5 × 10 −10 S cm −1 (293 K) is estimated. This value is by six orders of magnitude lower than the corresponding total conductivity σtotal = 10 −3 S cm −1 of Ga‐LLZO. Thus, it is concluded that the high values of σeon recently reported for similar systems do not necessarily mirror intragrain bulk properties of chemically homogenous systems but may originate from chemically inhomogeneous interfacial areas. Abstract : Garnet‐type ceramics represent one of the most important ingredients for next‐generation all‐solid‐state batteries. They need to show a high ionic conductivity but an extremely low electronic conductivity. Here, chemically homogeneous Ga‐stabilized single crystals of the Li7 La3 Zr2 O12 family are used to measure the bulk electronic conductivity, which, fortunately, turned out to be six orders of magnitude lower than the total conductivity.